Perancangan Sistem Keamanan Rumah Pintar Menggunakan ESP8266 Berbasis IoT - Dinata, Ego Setia; Kalsum, Toibah Umi; Rozzi, Yoli Andi (Jurnal Multidisiplin Dehasen (MUDE), 2025)
The advancement of Internet of Things (IoT) technology has opened up new opportunities in developing more efficient and integrated home security systems. This research aims to design a smart home security system based on IoT using the NodeMCU ESP8266 microcontroller integrated with a PIR motion sensor, LED, and buzzer. The system is designed to detect suspicious motion around the house and provide real-time notifications to the user. In its implementation, the system utilizes Telegram as a security alert platform. When the PIR sensor detects motion, the NodeMCU activates the buzzer and LED as local alarms and sends an automatic message to the user's Telegram account. Additionally, the system features remote control via WhatsApp, allowing users to activate or deactivate the security system as needed.Test results show that the system can respond quickly to motion detection, trigger local alarms, send notifications via Telegram, and receive remote commands via WhatsApp reliably. With its simple design and low cost, this system offers an effective solution for enhancing home security in a smart and practical way